María Estela Guevara de Álvarez (ed.). Antología gnómica de la literatura griega. Líricos arcaicos, poetas monódicos y corales. 1ª ed. Ciudad Autónoma de Buenos Aires, Santiago Arcos, 2016, 182 pp. - Poquet, Adriana Claudia (2017)
Fil: Poquet, Adriana Claudia. Universidad Nacional de Cuyo